(untitled) (Modern education and development, 2025)
The liver is a vital organ that plays a crucial role in maintaining homeostasis within the human body. It is responsible for various physiological functions, including metabolism, detoxification, protein synthesis, and bile production. This article provides an overview of liver physiology and its essential functions.